COVID‐19 Screening with Chest CT in Acute Stroke Imaging: A Clinical Decision Model. Issue 5 (26th June 2020) - Qureshi, Adnan I.; French, Brandi R.; Siddiq, Farhan; Arora, Niraj A.; Nattanmai, Premkumar; Gomez, Camilo R.
ABSTRACT: BACKGROUND AND PURPOSE: Acute stroke patients may have undiagnosed coronavirus disease 2019 (COVID‐19) infection, transmissible to medical professionals involved in their care. Our aim was to determine the value of incorporating a chest computed tomography (CT) scan during acute stroke imaging, and the factors that influence this decision. METHODS: We constructed a probabilistic decision tree of the value of acquiring a chest CT scan or not, expressed in quality‐adjusted life months (QALM) of patients and medical professionals. The model was based on the chance of detecting infection by chest CT scan, the case fatality rates of COVID‐19 infection, the risk of COVID‐19 infection after exposure, the expected proportion of medical professionals exposed, and the exposure reduction derived from early disease detection. RESULTS: The decision to incorporate the chest CT scan was superior to not doing so (12.00 QALM vs 11.99 QALM, respectively), when the probability of patients having undetected COVID‐19 infection is 3.5%, potentially exposing 100% of medical professionals, and if early detection reduces exposure by 50%. The risk of developing symptomatic COVID‐19 infection following exposure casts uncertainty on the results, but this is offset by the potential for reducing exposure. CONCLUSIONS: We identified a measurable benefit of incorporating a chest CT into the urgent imaging protocol of acute stroke patients in reducing exposure of medical professionals without appropriate precautions. The clinical impact of this benefit, however, may not be materially significant.